The Iowa gambling task: real versus facsimile rewards and psychopathy - Bell, Taylor Doreen (2006)
The Iowa Gambling Task (Bechara, Damasio, Damasio, & Anderson, 1994) has been the foundation of much of the recent research on adaptive decision making in humans. This task was first described by Bechara et al. in their research on patients with ventromedial (VM) lesions. These investigators have found impairments in the decision making processes of those with VM lesions. The Iowa Gambling Task was developed in an attempt to quantify those adaptive decision making deficits and has since been used to study adaptive decision making in those with antisocial and aggressive personalities(Blair, 2004; Blair, Colledge, & Mitchell, 200); substance abusers (Bolla et al., 2002);children and age differences (Garon & Moore, 2004; Kerr & Zelazo, 2004); as well as instrumental and reactive aggression (Berkowitz, 1993, Raine et al., 1998). However,much remains to be understood about this experimental decision making task,specifically, the type of reinforcement provided. Bowman and Turnbull (2003) recently demonstrated that groups receiving real contingencies did not differ from a group that received imagined contingencies. However, we know that antisocial and psychopathic traits are related to both Iowa Gambling Task performance and the perception of positive and negative contingencies. This study examined the differences between real and facsimile reinforcers, while taking the personality of the individual into account. Similar results were found in comparison to Bowman and Turnbull's study in that participants learned the task over trials, however no significant difference was found between real versus facsimile reinforcers. Furthermore, scores on the Levenson Self-Report Psychopathy Scale and the M5 domains of Neuroticism, Extroversion, Agreeableness,and Conscientiousness did not result in significant improvement of selections between the facsimile condition and the cash condition.